Comparing molecular photofragmentation dynamics in the gas and liquid phases - Harris, Stephanie J; Murdock, Daniel; Zhang, Yuyuan; Oliver, Thomas A A; Grubb, Michael P; Orr-Ewing, Andrew J; Greetham, Gregory M; Clark, Ian P; Towrie, Michael; Bradforth, Stephen E; Ashfold, Michael N R (Physical chemistry chemical physics : PCCP, 2013)
This article explores the extent to which insights gleaned from detailed studies of molecular photodissociations in the gas phase (i.e. under isolated molecule conditions) can inform our understanding of the corresponding photofragmentation processes in solution. Systems selected for comparison include a thiophenol (p-methylthiophenol), a thioanisole (p-methylthioanisole) and phenol, in vacuum and in cyclohexane solution. UV excitation in the gas phase results in RX-Y (X = O, S; Y = H, CH3) bond fission in all cases, but over timescales that vary by ~4 orders of magnitude - all of which behaviours can be rationalised on the basis of the relevant bound and dissociative excited state potential energy surfaces (PESs) accessed by UV photoexcitation, and of the conical intersections that facilitate radiationless transfer between these PESs. Time-resolved UV pump-broadband UV/visible probe and/or UV pump-broadband IR probe studies of the corresponding systems in cyclohexane solution reveal additional processes that are unique to the condensed phase. Thus, for example, the data clearly reveal evidence of (i) vibrational relaxation of the photoexcited molecules prior to their dissociation and of the radical fragments formed upon X-Y bond fission, and (ii) geminate recombination of the RX and Y products (leading to reformation of the ground state parent and/or isomeric adducts). Nonetheless, the data also show that, in each case, the characteristics (and the timescale) of the initial bond fission process that occurs under isolated molecule conditions are barely changed by the presence of a weakly interacting solvent like cyclohexane. These condensed phase studies are then extended to an ether analogue of phenol (allyl phenyl ether), wherein UV photo-induced RO-allyl bond fission constitutes the first step of a photo-Claisen rearrangement.